THE ROLE OF SERVICE QUALITY AND CUSTOMER SATISFACTION IN PREDICTING CUSTOMER RETENTION INTENTION - Feranvin Osman; Alain Moelya Warisadi; Wei Ming Yeo; Keni Keni; Nicholas Wilson (Jurnal Bisnis dan Akuntansi, 2024)
This research aims to empirically test E-S-QUAL, bank service quality, and customer satisfaction on customer retention intention with gender as a moderating variable. The total sample in this study was 194 respondents, who were digital bank users in Jakarta who were collected by using Google Form. The sample were selected by using convenience sampling technique. The data analysis technique uses Partial Least Square-Structural Equation Modeling (PLS-SEM) by using SmartPLS4 software. The research results show that E-S-QUAL, bank service quality, and customer satisfaction influence customer retention intention positively among digital bank users. Next, E-S-QUAL and bank service quality have a positive influence on customer satisfaction. Furthermore, customer satisfaction mediates the positive influence of E-S-QUAL and bank service quality on customer retention intention among digital bank users. Finally, female gender can moderate the influence of E-S-QUAL and bank service quality on customer satisfaction among digital bank users. However, male gender can only moderate the influence of E-S-QUAL on customer satisfaction, but cannot moderate the influence of bank service quality on customer satisfaction.